Present and future of aquaculture vaccines against fish bacterial diseases - Toranzo A.E.; Romalde J.L.; Magariños B.; Barja J.L. (The use of veterinary drugs and vaccines in Mediterranean aquaculture, 2009)
The following aspects are described for each of the main bacterial diseases in which vaccination is employed: (i) the biochemical, antigenic and genetic heterogeneity of the etiological agents; (ii) their geographical distribution and host range; (iii) the effectiveness and problems of current commercial vaccines; and (iv) the new vaccination approaches using recombinant DNA technology or other strategies different to the classic bacterins. In addition, economic aspects and future trends related to fish vaccination are also addressed.
The Use of Veterinary Drugs and Vaccines in Mediterranean Aquaculture, 2003/05/21-23, Izmir (Turkey)